Digitization of small and medium-size restaurant enterprises: the mediating role of owner/manager IT skill and moderating influence of COVID-19 - Elikem Chosniel Ocloo; Isaac Sewornu Coffie; Zakari Bukari; Shani Bashiru (Cogent Business & Management, 2024)
PurposeThe purpose of this study is to empirically examine the moderating effect of the COVID-19 pandemic on SME digitization in the restaurant sub-sector of the hospitality industry. The study further seeks to examine the mediating role of owner/managers' skills and attitudes on the digitization efforts of SMEs.Design/methodology/approachData from 397 owners and nonowner executives of 261 restaurant SMEs were analyzed using Partial Least Square Structural Equation Modelling (PLS-SEM).FindingsThe findings show that the COVID-19 pandemic is a significant moderating factor that could positively influence SMEs in the restaurant sector to digitize their operations. The study found no direct relationship between digital strategy, competitive pressure, and SME digitization. However, the study's findings show that owner/managers' skills and attitude are a significant positive mediator for SME digitization.Research limitations/implicationsThe study is limited to one sector in the hospitality industry. Additional studies are required to analyze multi-source data from other SMEs to deepen our understanding of the influence of the COVID-19 pandemic on SME digitization. Other moderating and mediating variables could also be examined.Practical implicationsThe significant moderating influence of COVID-19 implies that restaurant SMEs could take advantage of the pandemic and move from the marketplace to market space by digitizing their operations. To achieve this, they need to invest in owner/managers' digital skills.Originality/valueTo the best of the authors' knowledge, the study is among the first to empirically examine the moderating influence of the COVID-19 pandemic on SME digitization from an emerging market context.
Keywords: 650; base view theory; digital strategy; hospitality industry; organizational culture; owner/manager IT skill; SME digitization